REAKSI PASAR MODAL SEBELUM DAN SESUDAH PERISTIWA UPACARA PEMBUKAAN ASEAN GAMES 2018 DI JAKARTA - Riyadi, Sugeng; Sujito, Sujito; Rinawati, Tri (Jurnal Dinamika Sosial Budaya, 2020)
The improvement of the capital market is impacted by a few capital market pointers, for example, capitalization esteems, the estimation of offers exchanged, and the stock value record. Changes from these factors will influence financial strength and political and security steadiness which mirror the dimension of certainty of monetary on-screen characters in household conditions, in this manner capital markets can influence the economy. This investigation utilizes an occasion consider examination technique. The estimation time frame utilized amid the opening function of the Asian Games 2018 in Jakarta. In this examination, the populace is all customer merchandise fabricating division organizations, nourishment and refreshment sub-segments on the Indonesia Stock Exchange (IDX). The examining system utilized immersed testing, which turned into the investigation test of 18 organizations. Specialized examination in the investigation utilizing an alternate test Paired Sample t-Test. In view of the consequences of the distinction test, the Abnormal Return normal and Trading Average Activity Volume when the Asian Games 2018 are the equivalent (not unique).